THE ORIGIN OF THE ABSURD THEATRE - Iskandarova Navbakhor Ilkhomovna (Web of Journals Publishing, 2024)
This paper deals with the issue of the origin of modern drama types, namely absurd theatre and its core that is related to philosophy. The importance of existentialism, which is the sub branch of philosophy, is analyzed throughout the article. Furthermore, different views, that were under the discussion of many philosophers and critics, on the term “absurd” are presented.
Keywords: absurd, existentialism, cleavage, essence, neo-realist; drama of non-communication; comedy of menace; dark comedy; drama of cruelty, chaotic.